Improving the ACGIH threshold limit value (TLV) process. (9th October 2018) - Smith, Carr J; Perfetti, Thomas A
The intent of this manuscript is to elucidate needed improvements in American Conference of Governmental Industrial Hygienists (ACGIH) threshold limit value (TLV) deliberations. More broadly, irreproducibility and bias adversely impact the collection, interpretation, statistical analysis, presentation, and reporting of results in many fields. In 2012, Begley and Ellis reported that scientists at Amgen had attempted to confirm published findings related to research topics of possible interest to Amgen. Fifty-three papers were deemed "landmark" studies. The authors were "shocked" when scientific findings were confirmed in only 6 (11%) cases. Many studies have confirmed that the peer-reviewed literature in biomedicine is in the midst of an irreproducibility crisis. Compounding the irreproducibility crisis is the existence of a significant bias against the publication of negative results. In the toxicology setting, negative toxicity test results are infrequently published as compared with reports that a chemical possesses a particular toxicity in a given test. Despite these deficiencies, the ACGIH states that "…the TLV ® -CS Committee preferably relies on published, peer reviewed literature available in the public domain." The primarily academic studies published in the peer-reviewed literature upon which ACGIH relies to determine TLVs rarely report raw data not already statistically transformed that are thus incalculable. In contrast, consideration of unpublished studies funded by industry, the vast majority of which are good laboratory practice-conducted contract lab studies, is only acceptable to ACGIH if the data owner provides the raw data to third parties upon request. This asymmetry in both the source of data emphasized, and inability to independently statistically analyze findings reported in the published academic literature, introduces a strong skew toward reliance on unverifiable although published measurements in the TLV process. Since Occupational Safety and Health Administration (OSHA) recommends that workplaces rely on ACGIH TLVs and National Institute for Occupational Safety and Health recommended exposure limits rather than older OSHA permissible exposure limit values to optimize worker safety, ACGIH should adopt a more transparent and science-based process.